2015
DOI: 10.1002/hep.28257
|View full text |Cite
|
Sign up to set email alerts
|

Engineered fibroblast growth factor 19 reduces liver injury and resolves sclerosing cholangitis in Mdr2‐deficient mice

Abstract: Defects in multidrug resistance 3 gene (MDR3), which encodes the canalicular phospholipid flippase, cause a wide spectrum of cholangiopathy phenotypes in humans. Mice deficient in Mdr2 (murine ortholog of MDR3) develop liver diseases that closely reproduce the biochemical, histological, and clinical features of human cholangiopathies such as progressive familial intrahepatic cholestasis and primary sclerosing cholangitis. We hypothesized that modulating bile acid metabolism by the gut hormone fibroblast growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 57 publications
5
103
0
Order By: Relevance
“…Given that both adiponectin and Fgf15 exhibited potent anti-inflammatory properties (15,16,(45)(46)(47), elevation of circulating adiponectin and Fgf15 in the ethanol-fed mNTKO mice might also synergistically or additively trigger an anti-inflammation signaling network and protected mNTKO mice from ethanol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that both adiponectin and Fgf15 exhibited potent anti-inflammatory properties (15,16,(45)(46)(47), elevation of circulating adiponectin and Fgf15 in the ethanol-fed mNTKO mice might also synergistically or additively trigger an anti-inflammation signaling network and protected mNTKO mice from ethanol-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are increasingly being recognized as the most sensitive markers of inflammation and liver dysfunction and injury (45,46). Conceivably, the normalized hepatic and serum bile acids in the ethanol-fed mNTKO mice might limit accumulation of toxic bile acids such as deoxycholic acid in liver and ultimately ameliorated ethanolinduced liver damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that although FGF19 downregulates BA synthesis, it induces hepatocyte proliferation and prolonged exposure in animal studies has been shown to cause hepatocellular carcinoma [33] . This potential tumorigenic action of FGF19 is of a concern but circumvented by recent development of engineered FGF19 variants without mitogenic actions [34] . Pre-clinical studies suggest FGF19 analogues have potential in the treatment of PBC and PSC.…”
Section: Other Therapiesmentioning
confidence: 99%
“…This hormone, when released from the gut, binds to the tyrosine kinase receptor FGF receptor 4/β-Klotho on hepatocytes, which activates the jun N-terminal kinase 1/2 signaling pathway [53]. Intestinal FXR activation [54] and the FGF19 mimetic M70 [55,56] dampen cholestatic liver injury by strongly reducing hepatic bile acid synthesis and the circulating bile acid pool. So, mouse studies clearly show hepatoprotection through (gut-specific) FGF15/19 signaling, primarily by reducing bile acid pools, sharing its mode of action with ASBT-inhibition.…”
Section: Inhibition Of Bile Acid Uptake To Ameliorate Cholestatic LIVmentioning
confidence: 99%